Микропроцессорные системы: учебное пособие для вузов - Александров Е. К. Евгений Константинович; Грушвицкий Р. И. Ростислав Игоревич; Куприянов М. С. Михаил Степанович; Мартынов О. Е. Олег Евгеньевич; Панфилов Д. И. Дмитрий Иванович; Ремизевич Т. В. Татьяна Вячеславовна; Пузанков Д. В. (Учебное пособие для вузов)
Авт. указ. на обороте тит. л.